Improvement of Shooting Techniques on Free Throw Line in Basketball Game - Masayu Rizka Risjanna; Dadan Mulyana; Widi Kusumah (STKIP Muhammadiyah Kuningan, 2021)
In a basketball game, shooting is an element that determines a team's victory. One of the shooting techniques in basketball is the free-throw technique. Purpose: This study aimed to assess the improvement of free-throw processes in basketball games using the ring modification method. Methods and Material: This study uses a quantitative approach with experimental methods with the pre-test post-test control group design. Statistical analysis used: the pre-test and post-test were carried out using a shooting skill assessment scale instrument in basketball games, and then treatment is given. Result: The average increase in the experimental group is better than the control group after treatment is delivered. Conclusion: the results of the study show that ring modification can affect improving shooting techniques from the free-throw line on basketball extracurricular activities at SMP Negeri 5 Bandung.